2007
DOI: 10.1111/j.1468-0297.2007.02089.x
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Budget Rules and Aggregate Instability: The Role of Consumption Taxes

Abstract: It is known that in a real business cycle model with constant returns to scale and a balanced budget fiscal policy rule, steady state indeterminacy may arise due to endogenous labour income tax rates. This article shows that when the government finances its expenditures via an endogenous consumption tax instead, a steady state is always saddle-path stable. Consequently, combining income taxes with consumption taxes makes the ranges of indeterminacy shrink, thus reducing the possibility of aggregate instability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 16 publications
1
77
2
Order By: Relevance
“…Lin's examination is focused on the effects of changes in some parameters on the steady state; while this study is focused on effects of changes in some parameters on the dynamic paths of the economic system as well as on the equilibrium point. Almost of all the recent theoretical literature of dynamic interactions between economic growth and public debts use either the Ramsey framework in continuous time (Cohen and Sachs, 1986;Blanchard and Fischer, 1989;Barro et al 1995;Semmler and Sieveking, 2000;Guo and Harrison, 2004;and Giannitsarou, 2007) or the OLG modeling framework in discrete time (Diamond, 1965;Farmer, 1986;Turnovsky and Sen, 1991;Azariadis, 1993;de la Croix and Michel, 2002;and Chalk, 2000). Different from the traditional approaches to household decision, this study uses Zhang's approach to household decision to re-examine the debt issues addressed by Diamond (1965).…”
Section: Introductionmentioning
confidence: 99%
“…Lin's examination is focused on the effects of changes in some parameters on the steady state; while this study is focused on effects of changes in some parameters on the dynamic paths of the economic system as well as on the equilibrium point. Almost of all the recent theoretical literature of dynamic interactions between economic growth and public debts use either the Ramsey framework in continuous time (Cohen and Sachs, 1986;Blanchard and Fischer, 1989;Barro et al 1995;Semmler and Sieveking, 2000;Guo and Harrison, 2004;and Giannitsarou, 2007) or the OLG modeling framework in discrete time (Diamond, 1965;Farmer, 1986;Turnovsky and Sen, 1991;Azariadis, 1993;de la Croix and Michel, 2002;and Chalk, 2000). Different from the traditional approaches to household decision, this study uses Zhang's approach to household decision to re-examine the debt issues addressed by Diamond (1965).…”
Section: Introductionmentioning
confidence: 99%
“…23 Hence, not only configurations (i) to (iv) are possible, but configurations (v) and (vi) may also emerge. These last two configurations require that α ΓL < α * ΓL as shown in (21). They are possible in the absence of distortions on Ω, whereas they never emerge without effects through Γ, since α *…”
Section: Distortions On the ω And γ Functionsmentioning
confidence: 99%
“…20 In Grandmont et al (1998), the consequences of indeterminacy and bifurcations for the existence and properties of equilibria, in particular those exhibiting deterministic and stochastic expectations-driven cycles, are explored. 21 Indeterminacy requires D < 1. Since D is increasing with ε γ , D 1 (σ) < 1 is needed, which is equivalent to σ > σ H1 when D ′ 1 (σ) < 0 as in Table 1.…”
Section: By Inspection Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility to avoid an indeterminate equilibrium path is to assume that it is the consumption tax that is adjusted in a way such that the government budget is balanced at each point in time, as demonstrated by Giannitsarou (2007). There, it is shown that the economy is always characterized by a unique saddle-point stable growth path.…”
Section: Introductionmentioning
confidence: 99%